Gender concerns in the postproduction of selected horticultural crops in the Philippines and Thailand: Issues and perspectives - Zenaida F Toquero Rebecca C Torres (SEAMEO SEARCA, 1998)
The book is a synthesis of research results from an International Development Research Centre-funded project on "Women in postproduction systems". Special emphasis is gives to the stutus and role of women in postproduction activities